Prototype Alat Pendeteksi Kebakaran Menggunakan Sensor Flame dan MQ-2 Berbasis Arduino Uno - Nugraha, Denny Andian; Satria, Budy (AI Society & STMIK Indonesia, 2022)
Fires can occur due to uncontrolled activities such as short circuits, littering of cigarette residues, gas leaks, human carelessness and natural factors that cause fires to appear. This research aims to design a prototype fire detector using a flame sensor to detect fire and an MQ-2 sensor to detect smoke and gas based on the Arduino Uno microcontroller. When these sensors detect the presence of fire, smoke and gas objects, the Buzzer and LEDs that have been programmed into indicators will be active as an early warning that a fire has occurred. The results of the tests that have been carried out in this study are the Arduino Uno Microcontroller works well to perform data processing. Testing the flame sensor at a distance of 5-25 cm causes the alarm to sound and the LED lights up as an indicator that the sensor is functioning in detecting hotspots. The MQ-2 sensor successfully detects the presence of smoke and gas at a density value of 760-775ppm. So this tool can help in providing a fire warning.